Penerapan Model Pembelajaran Active Learning Tipe Team Quiz Untuk Meningkatkan Kreativitas Siswa Pada Mata Pelajaran IPAS Kelas IV SDN 167 Pekanbaru - Alinna Alinna; Deprizon Deprizon; Salman Salman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine the application of the team quiz type active learning learning model in increasing learning creativity and science knowledge of class IV students at SDN 167 Pekanbaru. This research uses the action research method which was carried out at SDN 167 Pekanbaru for the 2023/2024 academic year. Research was carried out through planning, action implementation, observation and evaluation stages. The subjects of this research were determined using purposive sampling, namely class VI A SDN 167 Pekanbaru, totaling 35 people. Data was collected using student activity observation sheets and knowledge tests. The collected data was analyzed using quantitative and qualitative descriptive analysis. The results of the research show that the team quiz type active learning model can increase the creativity of class VI students at SDN 167 Pekanbaru. in science and science learning was 17.50% and students' knowledege were 34.00%.